Design of Arbitrarily Shaped Planar Microstrip Antenna Arrays with Improved Efficiency - Sheng Ye; Xianling Liang; Wenzhi Wang; Junping Geng; Ronghong Jin; Y. Jay Guo; Trevor S. Bird (International Journal of Antennas and Propagation)
A design technique is described for an arbitrarily shaped planar microstrip antenna array with improved radiation efficiency. In order to fully utilize the limited antenna aperture, several basic modules are proposed from which we construct the array. A consideration of the aperture shape shows that with several practical examples a proper combination of these basic modules not only allows the convenient design of arbitrarily-shaped microstrip array, but also helps to improve the aperture radiation efficiency. To confirm the feasibility of the approach, a circular array with 256 elements was constructed and fabricated. Both computed and measured aperture radiation results are compared and these demonstrate that the design technique is effective for arbitrarily-shaped planar microstrip arrays.